IMPLICATIONS OF MULTIPLE MINISTERIAL POSITIONS ON THE INDONESIAN GOVERNMENT SYSTEM FROM THE PERSPECTIVE OF AL-MAWARDI - Nursarah A Conoras; Darussalam Syamsuddin; Dea Larissa (Jurnal Al Tasyri'iyyah, 2025)
This study aims to explain the implications of dual ministerial positions on the Indonesian government system and to examine the implications of dual ministerial positions on the Indonesian government system from al-Mawardi's perspective. This is a qualitative study. The research design is field research. The results of this study indicate that dual ministerial positions have the potential to cause conflicts of interest, reduce professionalism in policy-making, and weaken the principles of good governance. Therefore, it is necessary to strengthen regulations that explicitly prohibit dual positions in order to improve the effectiveness of governance and maintain the integrity of public officials. Imam Al-Mawardi emphasizes professionalism, justice, and efficiency in governance. According to him, holding multiple positions indicates an imbalance of duties or personal ambition that may disregard the interests of the people. Although he does not explicitly prohibit it, he considers the practice unethical and potentially disruptive to the stability and effectiveness of government.